Ambiguity Found In Creative English Textbook: Content Analysis - Fatimah, Riza; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
This study deals with the ambiguity that is found in Creative English textbook. The aims of this research are (1) to describe the types of ambiguity, (2) to describe the frequency of each types of ambiguity, (3) to describe the dominant types of ambiguity, (4) to describe the causes of the ambiguous sentences, and (5) to describe the ways to disambiguate ambiguity. The type of this research is descriptive qualitative research. The data of this research are all ambiguous English words, phrases, or sentences which found in Creative English textbook. The data collection technique is documentation. The technique of data analysis is descriptive qualitative. The researcher uses the theories of Kreidler, Fauziati, Prideaux and Baker to analyze the types of ambiguity. The results of the research show that (1) the researcher finds all the types of ambiguity, there are: lexical ambiguity, referential ambiguity, surface structure ambiguity, and deep structure ambiguity; (2) the frequency of each type of ambiguity are lexical ambiguity consists of 34 ambiguous sentences (17, 44%), referential ambiguity consists of 140 ambiguous sentences (71, 79%), surface structure ambiguity consists of 17 ambiguous sentences (8, 72%), and deep structure ambiguity consists of 4 ambiguous sentences (2, 05%); (3) the dominant types of ambiguity is referential ambiguity; (4) the causes of ambiguity are without context, ambiguous word order, improper or missing punctuation, and faulty pronoun reference; and (5) the ways to disambiguate the ambiguous sentences are by using paraphrasing, adding preposition, moving sentence construction, adding additional context, and using picture.